The Graphics Processor Industry: A Study On The Success,Failures, And Future Trends - Chan, Weng Jun (2007)
This study provides extensive coverage on three key aspects of the graphics processor industry: Success,Failures,andthe Future Trends. A total of seven world renowned graphics chip makers have been selected for the author's research.